Physicochemical Characteristics of Wood Vinegars from Carbonization of Leucaena leucocephala, Azadirachta indica, Eucalyptus camaldulensis, Hevea brasiliensis and Dendrocalamus asper - Theapparat, Yongyuth; Chandumpai, Ausa; Leelasuphakul, Wichitra; Laemsak, Nikhom; Ponglimanont, Chanita (Agriculture and Natural Resources, 2014)
The physicochemical characteristics were evaluated of eight wood vinegars from the carbonization of five wood species—Leucaena leucocephala (Katin), Azadirachta indica (Sadao), Eucalyptus camaldulensis, Hevea brasiliensis (rubber wood) and Dendrocalamus asper (bamboo). The vinegars were produced by heating wood samples up to 400 °C in a Thai-Iwate kiln and were compared with two commercial products. The quality assessments of all wood vinegars were determined according to criteria from the Charcoal Handbook. The results showed that all wood vinegar samples appeared to be good quality in terms of odor, color and transparency. The pH (2.9–3.5) and total soluble tar (0.325–0.963 % by weight) also met the standard criteria for the pH (around 3) and total soluble tar (not more than 3%). The values of the specific gravity of only two products, from rubber wood (1.012 g.mL-1) and bamboo (1.010 g.mL-1) were within the acceptance criteria of 1.010–1.050 g.mL-1. Chemical compositions of wood vinegars as determined qualitatively by gas chromatography/mass spectrometry and quantitatively by gas chromatography/flame ionized detector consisted of acetic acid as the largest component (30.45–70.60 mg.mL-1). A high number of phenol derivatives (16 compounds) were found and those in higher concentrations were 4-propyl-2-methoxyphenol (5–11 mg.mL-1) followed by 2-methylphenol (2–4 mg.mL-1). An acetic acid concentration from the eight samples whose presence was indicated by pKa at 4.7 was mainly responsible for the pH values as shown in the good correlations of plots between pH and acetic acid concentrations (Correlation coefficient, R = 0.92). The total acid contents of the ten wood vinegars as determined by titration with 0.1 N sodium hydroxide showed poor correlations with pH (R = 0.65) due to the presence of a variety of organic acids and phenolic compounds which may have affected proton transition. The specific gravity showed good correlations with total soluble tar and degree Brix (R = 0.87 for both); in turn the degree Brix showed good correlation with the total soluble tar (R = 0.87). Thus, the degree Brix which was easy to determine could be used as a general indicator of total soluble tar. The amount of total soluble tar signified the presence of phenolic compounds, of which previous studies suggested antifungal activity and usefulness as wood preservatives. Phenolic compounds were also confirmed by the ultraviolet absorption maximum (λmax) at 268–274 nm.